Hippocampal infarction: Identification of three new types - Förster, Alex; Al-Zghloul, Mansour; Eisele, Philipp; Wenz, Holger; Böhme, Johannes; Groden, Christoph; Neumaier-Probst, Eva (Journal of neuroradiology, 2018)
Background and purpose: Hippocampal infarction (HI) is common but yet still not comprehensively studied. In the present study, we aimed to identify novel HI patterns and to describe additional ischemic lesions outside the Hippocampus to draw conclusions regarding the underlying vessel occlusion. Methods: In 222 patients (mean age 69.9 (±13.6) years; 129 (58.1%) male, 93 (41.9%) female) with HI, diffusion-weighted images were analyzed with emphasis on HI patterns and associated ischemic lesions outside the hippocampus. HI were classified as type 1 (complete), 2 (lateral), 3 (dorsal), and 4 (circumscribed). Further possible HI patterns were defined and classified as type (ventral), 6 (ventrolateral), and 7 (dorsolateral). Results: Unilateral HI was found in 218 (98.2%) patients. In these, type 5 and 6 were identified in 5 (2.3%) patients, and type 7 in 8 (3.7%) patients respectively. Type 1 was found in 62 (28.4%), 2 in 53 (24.3%), 3 in 57 (26.1%), and 4 in 28 (12.8%) patients. Further ischemic lesions were found in the territory of the anterior cerebral artery (3.6%), middle cerebral artery (14.9%), anterior choroidal artery (AChA) (7.2%), posterior cerebral artery (89.6%), and in the brainstem (6.3%) and cerebellum (20.3%). Type 5 and 6 were significantly associated with acute ischemic lesions in the AChA territory (6/10 (60%) vs. 11/200 (5.5%), P<0.001). Conclusions: We identified three novel HI types. Probably, type 5 and 6 can be attributed to occlusion of the AChA. Overall, these HI types are rare, possibly due to a better collateralization in the case of AChA occlusion.